Growth Response of Potato Cuttings (Solanum Tuberosum L.) Granola Lembang Varieties Results Of Tissue Culture To Giving Radix Up With Different Segments - Putra, Faisal Haryanto; Ishartati, Erny; Husain, Syarief (Journal of Tropical Crop Science and Technology, 2019)
Potato plants are propagated vegetatively with tubers. The difficulty of getting potato seeds with tubers is an obstacle in the supply of potato seeds, to overcome these obstacles vegetative propagation with cuttings can be a solution for the supply of potato seeds. This research used a factorial Randomized Block Design (RBD). The first factor is the type of Radix Up consisting of 4 levels, namely Z0 (control), Z1 (Radix Up 1), Z2 (Radix Up 2), and Z3 (Radix Up 3), the second factor is the number of segments consisting of 3 levels namely D1 (number of segment 1), D2 (number of segment 2), and D3 (number of segment 3). Observation variables included: when the roots appeared, plant height, number of leaves, and stem diameter. The results showed that there was an interaction between Radix Up types and the number of segments on the growth of potato shoot cuttings when the roots appeared, but there were no interactions on other observational variables. The Z1D3 treatment (Radix Up 1 and segment number 3) gives the fastest average value, which is the average when the root appears 4.33 days.